As mulheres sob o capital: o papel do trabalho doméstico na relação entre a opressão das mulheres e a exploração capitalista - Barbosa, Carolina Marques (2021)
The issue of women in capitalist society is framed by several challenges in daily women's lives. So far, studies on this subject have been massively developed by post-modern theories and do not cover the historical-social totality that comprises the oppression between both genders. It is urgent to carry out analyzes from the perspective of class, based on the concepts of political economy, to understand how oppression and exploitation are related in the structure of the capitalist social organization. This study developed a theoretical-conceptual investigation, based on historical-dialectical materialism, to discuss the maintenance and deepening of women’s oppression as a guarantee of capitalist exploitation, investigating how the Marxist literature has understood domestic unpaid work as the link between women's oppression and capitalist exploitation. Thus, this study developed a historical review of the genesis oppression between genders, placed in the class struggle, as well as the analysis of political economy categories to discuss how unpaid domestic work articulates the oppression of women and capitalist exploitation. It was noticed that oppression goes side-by-side with the possibility of exploiting the work of others. The division of society into classes sets the moment when the opposition between men and women was born, and since then, oppression and exploitation have been interchanged inseparably. It was also understood that the oppression experienced by women, together with other oppression experienced by the working class, is incorporated and adapted to capital, making up its central contradiction. Therefore, capitalism will develop a reproductive policy, based both on violence and on ideology, in which domestic work and its naturalization as a female workrole fulfill the function of keeping the workforce value reduced and increasing expropriation of relative surplus-value, establishing the oppression of women as a vehicle of capitalist exploitation.